Does Inferior Oblique Muscle Overaction Affect Ocular Vestibular Evoked Myogenic Potentials? - Demir, İsmail and Yalcin, Muhammed Zeki and Cengiz, Deniz Uğur and Aydın, Şükrü and Çankaya, Cem and Tekin, Ahmet Mahmut (European Journal of Therapeutics, 2023)
Objectives: Inferior oblique muscle overaction (IOOA) is a common ocular motility disorder. Ocular Vestibular Evoked Myogenic Potentials (oVEMP) are tests that evaluate the reflex pathway between the utricular macula and the inferior oblique muscle to detect vestibular diseases. Our study is of great importance as it is the first study in the literature to evaluate the effect of inferior oblique muscle overaction on oVEMP parameters. Methods: Thirty-five patients with unilateral inferior oblique muscle overaction (IOOA group) and 18 healthy volunteers without any neurological or vestibulocochlear disease were included in this study. All patients and healthy volunteers were evaluated with oVEMP. Results: No statistically significant difference was found between the n1 latency, p1 latency, n1-p1 latency measurement values of the participants included in the study (p>0,05). A statistically significant difference was found between the n1-p1 amplitude measurement values of the participants in patient groups (non-squint eyes, squint eyes) and control groups (p-value was 0.038). Conclusion: In IOOA patients, vestibulo-ocular reflex pathway may be affected, vestibular symptoms may develop thus o-VEMP responses may be affected. A careful anamnesis should be taken in IOOA patients, and it should be kept in mind that n1-p1 amplitudes and asymmetries may be significantly higher when o-VEMP is performed Keywords: o-VEMP, Strabismus, Inferior oblique muscle overaction, Balance, Vertigo